THE SOCIAL CONSTRUCTION OF ALI MUSTAFA YA’QUB’S HADITH THOUGHT: Internalisation, Externalisation, and Objectification in Contemporary Indonesia - Nurhidayah, Nurhidayah; Ziah, Nur; as-Sayyid, Muhammad Ahmad Abdulhadi (Ilmu Hadis, Fakultas Ushuluddin, Universitas Islam Negeri (UIN) Sunan Kudus, 2026)
This study examines the influence and recognition of the hadith thought of Ali Mustafa Ya’qub in Indonesia through the social construction theory of Peter L. Berger and Thomas Luckmann. Previous studies identify him as a leading contemporary Indonesian hadith scholar and a key figure in revitalising hadith studies, with Al-Thuruqu al-Shahihah fi Fahmi al-Sunnah al-Nabawiyah regarded as one of his most influential works. This paper explores how his ideas developed from personal reflection into an accepted scholarly methodology. The study argues that Ali Mustafa Ya’qub’s thought reflects the three dialectical stages of social construction. First, internalisation occurred as he absorbed historical sources, the views of earlier Muslim scholars, and insights gained from his academic experiences in Riyadh and travels to 33 countries, leading him to emphasise the social and geographical context of hadith interpretation. Second, externalisation took place through the publication of Al-Thuruqu al-Shahihah, which articulated and disseminated his interpretive approach. Third, objectification was achieved when his ideas gained institutional legitimacy through their adoption as required reading in the Darus-Sunnah Islamic boarding school and Islamic higher education institutions (PTKIN). The findings demonstrate that social construction theory provides a useful framework for explaining how individual scholarly ideas develop into an institutionalised and widely recognised methodology within contemporary Indonesian hadith studies.Penelitian ini mengkaji pengaruh dan pengakuan terhadap pemikiran hadis Ali Mustafa Ya’qub di Indonesia dengan menggunakan teori konstruksi sosial Peter L. Berger dan Thomas Luckmann. Sejumlah penelitian terdahulu menempatkannya sebagai salah satu ulama hadis Indonesia kontemporer yang berperan penting dalam revitalisasi kajian hadis, dengan Al-Thuruqu al-Shahihah fi Fahmi al-Sunnah al-Nabawiyah sebagai salah satu karya paling berpengaruh. Artikel ini menjelaskan bagaimana gagasannya berkembang dari refleksi individual menjadi sebuah metodologi yang diterima secara luas. Penelitian ini berargumen bahwa pemikiran Ali Mustafa Ya’qub mencerminkan tiga tahap dialektika dalam teori konstruksi sosial. Pertama, internalisasi terjadi ketika ia menyerap sumber-sumber historis, pandangan para ulama terdahulu, serta pengalaman akademiknya di Riyadh dan perjalanan ke 33 negara, yang membentuk pandangannya bahwa pemahaman hadis harus mempertimbangkan konteks sosial dan geografis. Kedua, eksternalisasi berlangsung melalui penerbitan Al-Thuruqu al-Shahihah fi Fahmi al-Sunnah al-Nabawiyah, yang menjadi media penyebaran pendekatan interpretasinya. Ketiga, objektivasi tercapai ketika gagasannya memperoleh legitimasi kelembagaan melalui pengadopsian karyanya sebagai bahan ajar wajib di Pondok Pesantren Darus-Sunnah dan Perguruan Tinggi Keagamaan Islam Negeri (PTKIN). Temuan penelitian menunjukkan bahwa teori konstruksi sosial merupakan kerangka analitis yang efektif untuk menjelaskan bagaimana gagasan seorang sarjana berkembang menjadi metodologi yang terlembagakan dan diakui secara luas dalam kajian hadis kontemporer di Indonesia.